A Psycholinguistic Perspective Of English Learning By Student Of Smpn 1 Sukamaju Luwu Utara - Sitti Halijah; Lusy Angreani; Ernawati Ernawati (Fakultas Sastra - Universitas Muslim Indonesia, 2016)
This research learned about kinds English learning as a foreign language wich are found at SMPN 1 Sukamaju. And, kinds of external effects in English Learning at SMPN 1 Sukamaju. The method of this research was quantitative method wich was conducted by questionnaire, the population of this research was the data after collected the data the researcher gave descriptive based on the steps of data analysis. Some kinds of learning strategis of English learnig as a foreign language were found at SMPN 1 Sukamaju in four class (VII E, VII F, VII G, VII H), namely, memori, cognitive, meta-cognitive, effective strategis, and social strategis. And, the researcher also found some kinds of external effect at SMPN 1 Sukamaju in those classes, namely, discipline, motivation from the teacher, condition of class and friends.